Inclusive Education in Rural Indonesia: Bridging Policy Gaps through Islamic Educational Perspectives on Disability - Mukaffan; Isnadi; Bahrul Munib (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to examine the implementation of inclusive education in rural Indonesia by focusing on the policy–practice gap and exploring how Islamic educational perspectives can contribute to bridging educational inequalities for children with disabilities. Specifically, it investigates how structural, socio-cultural, and governance-related factors shape access to inclusive education in peripheral village contexts. This research employs a qualitative approach with a case study design conducted in Wonorejo Village, Banyuputih District, Situbondo Regency. Data were collected through in-depth interviews with key stakeholders, including village officials, teachers, parents, and disability activists, as well as participant observation and document analysis. The data were analyzed using an interactive model involving data condensation, data display, and conclusion drawing, complemented by thematic analysis to identify patterns related to policy gaps, structural barriers, and Islamic educational values. The findings reveal that inclusive education in rural areas is characterized by multi-layered exclusion resulting from geographical isolation, limited infrastructure, weak local governance, and the absence of accurate disability data. Despite the existence of national and regional policies supporting inclusive education, their implementation at the local level remains largely symbolic and administrative. The study identifies a significant policy–practice gap, where inclusive education is not supported by adequate institutional readiness, teacher competence, or accessible facilities. Additionally, socio-economic constraints and cultural factors further limit the participation of children with disabilities in formal education. This study introduces a village-based analytical framework that shifts the focus from school-centered approaches to community and governance-based perspectives in understanding inclusive education. It also offers a novel theoretical contribution by integrating Islamic educational values, particularly justice (al-‘adl), equality (al-musawah), and universal compassion (rahmatan lil ‘alamin), as a normative foundation for inclusive education in Muslim-majority contexts. This study contributes theoretically by bridging global inclusive education discourse with Islamic educational philosophy, empirically by providing evidence from a rural and underrepresented context, and practically by proposing a village-based inclusive education model that emphasizes local governance, data-driven planning, and community participation. These contributions offer a more context-sensitive and culturally grounded approach to addressing educational inequality in rural areas.